Ethical Decision-Making: The Role of Self-Monitoring, Future Orientation, and Social Networks - Bon,Ana Carla (2017)
Abstract This study examines the influence of individual factors (self-monitoring, temporal orientation) on social networking, and their relationship with unethical decision-making. The study used surveys to measure the unethical intentions and social network data of 129 professionals. Data were analyzed using confirmatory factor analysis and structural equation modeling. The findings provided evidence that individual factors influence the development of social networks and, along with self-monitoring, the likelihood of unethical decision-making. In particular, being in positions of lower network centrality increased individuals' risk of unethical intention. One explanation stems from the need for high situation control to reduce risk and ensure the success of an event, which only a closed network can provide. However, ethical low self-monitor women were also found to have low centrality, so social networks alone do not explain ethical decision-making. This research represents a step forward in our understanding of ethical decision-making through the adoption of multiple and simultaneous factors, proposing an integrated theory of individual and situational factors influencing unethical options.